2020
DOI: 10.32924/ijbs.v3i3.98
|View full text |Cite
|
Sign up to set email alerts
|

"WAZZ Up Doc?" Cost Efficient, User Friendly, Patient Trust Level Based on Convenience and the Use of Hypnotherapy Mobile Apps Method

Abstract: Counseling method that uses a breakthrough unconscious forces, called hypnotherapy, is very effective in dealing with psychosomatic history. The reason patients' reluctance to visit specialist counseling and therapy; such a negative stigma, negative social perception, shame somebody to public judgment about mental illness, heavy traffic conditions and geographical distance between patient and psychologist, as well as the affordability of the financial condition of the patient. Effective solutions related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This statement is supported by research that found the effect of hypnotherapy on learning motivation of elementary school students, Semarang. There is a significant difference in the change or increase in learning motivation between the group receiving hypnotherapy therapy and the group not receiving hypnotherapy therapy (Imelda et al, 2019). Furthermore, another study tested Hypnoteaching on Student Motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This statement is supported by research that found the effect of hypnotherapy on learning motivation of elementary school students, Semarang. There is a significant difference in the change or increase in learning motivation between the group receiving hypnotherapy therapy and the group not receiving hypnotherapy therapy (Imelda et al, 2019). Furthermore, another study tested Hypnoteaching on Student Motivation.…”
Section: Introductionmentioning
confidence: 99%